Congruency sequence effects are driven by previous-trial congruency, not previous-trial response conflict - Weissman, Daniel; Carp, Joshua (Frontiers in Psychology, 2013)
Congruency effects in distracter interference tasks are often smaller after incongruent trials than after congruent trials. However, the sources of such congruency sequence effects (CSEs) are controversial. The conflict monitoring model of cognitive control links CSEs to the detection and resolution of response conflict. In contrast, competing theories attribute CSEs to attentional or affective processes that vary with previous-trial congruency (incongruent vs. congruent). The present study sought to distinguish between conflict monitoring and congruency-based accounts of CSEs. To this end, we determined whether CSEs are driven by previous-trial reaction time (RT)—a putative measure of response conflict—or by previous-trial congruency. In two experiments using a face-word Stroop task (n = 49), we found that current-trial congruency effects did not vary with previous-trial RT independent of previous-trial congruency. In contrast, current-trial congruency effects were influenced by previous-trial congruency independent of previous-trial RT. These findings appear more consistent with theories that attribute CSEs to non-conflict processes whose recruitment varies with previous-trial congruency than with theories that link CSEs to previous-trial response conflict.